2017
DOI: 10.1590/s0100-736x2017000600020
|View full text |Cite
|
Sign up to set email alerts
|

Influence of prolonged flaxseed ( Linum usitatissimum ) consumption over epididymis and testicle histoarchitecture of Wistar rats

Abstract: Flaxseed is considered a functional food with several health benefits. However, because of its high phytoestrogen content, flaxseed influences hormone metabolism and affects the gonadal biomorphology. In this study, computerized histomorphometry was used to evaluate seminiferous and epididymal tubules, considering the different regions of the epididymis (head, body and tail) of rats subjected to a prolonged diet of flaxseed. Young adult male Wistar rats (n=20) were divided into 2 groups during their lactation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…The TD and LD were measured using the average of two perpendicular lines. The EH was evaluated by the mean of four measurements in the epithelium (25).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TD and LD were measured using the average of two perpendicular lines. The EH was evaluated by the mean of four measurements in the epithelium (25).…”
Section: Methodsmentioning
confidence: 99%
“…The intermediate filaments of the Sertoli cells were labelled with vimentin and counted by the Cell Counter plugin of the Image J program. The mean number of cells counted per tubule of each experimental group was calculated according to the method proposed by Corrêa et al (25).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Cardozo et al (2012) observed an increase in estradiol after a prolonged Advances in Animal and Veterinary Sciences intake of 25% flaxseed. Furthermore, Corrêa et al (2017) found that the prolonged exposure to flaxseeds induced a significant increase in serum estradiol levels in rat.…”
Section: Effect Of Linseed Oil and Fluconazole On Lh Receptor (Lhr) A...mentioning
confidence: 96%
“…No presente estudo, não foram observadas alterações histomorfométricas epididimárias relacionadas ao diâmetro do túbulo, lume e altura do epitélio nas regiões avaliadas em nenhum dos grupos tratados. Corrêa et al, (2017), encontraram resultados similares em ratos Wistar tratados com semente de linhaça, substância rica em isoflavonas. O fato de não ter ocorrido nenhuma alteração nos parâmetros histomorfométricos, pode estar relacionado a dose, idade dos animais e tempo de exposição, pois, segundo Cederroth et al (2012), muitos efeitos reprodutivos podem se manifestar anos ou até mesmo décadas após a exposição inicial a tais substâncias.…”
Section: Discussionunclassified